Staying vigorous until work is over: The role of trait vigour, day-specific work experiences and recovery - Niessen, Cornelia; Sonnentag, Sabine (Journal of Occupational and Organizational Psychology, 2008)
Staying vigorous throughout the day is important for work-related behaviour, subjective well-being, and for effective functioning in the family domain. This study examined trait vigour (i.e. a person's general level of vigour), day-specific workload (time pressure, work hours), and recovery resulting from unwinding during leisure time as predictors of day-specific vigour as experienced at the end of the working day. Seventy-five individuals from service and public administration organizations completed one general survey and daily surveys two times per day for five working days. Trait vigour, demographic variables and control variables (e.g. job control, home workload) were assessed in the general survey. Day-specific level of vigour, day-specific workload, and day-specific recovery were measured in the daily survey. Analyses following a hierarchical linear modelling approach showed that trait vigour, day-specific workload and recovery accumulated during the preceding evenings predicted an individual's level of vigour at the end of the working day, after controlling for a range of other variables (gender, age, job control, and home workload). Trait vigour and accumulated recovery experiences interacted significantly to predict vigour at the end of the working day, indicating that individuals high on trait vigour benefit most from recovery experienced over the course of several days. © 2008 The British Psychological Society.